Late Pleistocene paleosols in the extra-glacial regions of Northwestern Eurasia: Pedogenesis, post-pedogenic transformation, paleoenvironmental inferences. (15th January 2019) - Rusakov, Alexey; Sedov, Sergey; Sheinkman, Vladimir; Dobrynin, Dmitriy; Zinovyev, Evgeniy; Trofimova, Svetlana; Maksimov, Fedor; Kuznetsov, Vladislav; Korkka, Maria; Levchenko, Snezana
Abstract: Recent revision of the eastern boundary of the last glaciation of Eurasia opened new perspectives in the search of the paleopedological records in the north of Eastern Europe and Western Siberia. We studied paleosol-sedimentary sequences in the Upper Volga and Middle Ob basins as a regional paleoecological record for the Late Pleistocene thermochrons. Two key sections Cheremoshnik and Belaya Gora containing MIS3 and MIS5 paleosol units and additional section Koskovo 2 with polycyclic MIS3 paleosol were investigated. Their timescale are based on C14 and U/Th datings as well as on stratigraphic and paleobotanical correlations. Macro-, meso- and micromorphological observations together with fossil insects and plant macrofossil were used as paleoenvironment proxy. MIS3 paleosols show abundant redoximorphic and cryogenic features that allow interpreting them as gleyic Cryosols. Sub-fossil insects and plant macrofossil reflect the cold climate conditions. Three incipient Ah horizons in Koskovo 2 pedocomplex point to multiple phases of pedogenesis, correlative to the MIS3 paleosol levels in different sections of the Eurasian loess belt and to the major interstadials of the Middle Pleniglacial of the NW Europe MIS5 paleosols are also characterized by gleyzation and peat accumulation, in this case we suppose geomorphological control on hydromorphic pedogenesis; however paleosol in Belaya Gora has clear signs of polygenesis including the phase of clay illuviation. Insect and plant remains from the lower paleosol level of the Belaya Gora section show the transition from cold (terminal phase of MIS6) to warm first, and then to a moderately cold climate (within MIS5). The obtained results contribute to understanding of soil and landscape zonality in the largest plains of Eurasia mostly during the warm phases of Late Pleistocene.